Major Intrinsic Proteins in Fungi: A Special Emphasis on the XIP Subfamily - Jean-Stéphane Venisse; Gisèle Bronner; Mouadh Saadaoui; Patricia Roeckel-Drevet; Mohamed Faize; Boris Fumanal (Journal of Fungi, 2025)
The fungal kingdom, with an estimated five million species, has undergone extensive diversification over the past billion years and now occupies a wide array of ecological niches from terrestrial to aquatic ecosystems. To thrive in such diverse environments, fungi must exhibit finely tuned physiological and morphological responses orchestrated by conserved molecular pathways. Increasing evidence suggests that aquaporins (AQPs) play a key role in mediating these adaptive responses, particularly under varying abiotic and biotic stress conditions. However, despite notable advances in recent decades, the precise functional roles of AQPs within the fungal kingdom remains largely unresolved in the field of cell biology. AQPs are transmembrane proteins belonging to the major intrinsic proteins (MIPs) superfamily, which is characterized by remarkable sequence and structural diversity. Beyond their established function in facilitating water transport, MIPs mediated the bidirectional diffusion of a range of small inorganic and organic solutes, ions, and gases across cellular membranes. In fungi, MIPs are classified into three main subfamilies: orthodox (i.e., classical) AQPs, aquaglyceroporins (AQGP), and X-intrinsic proteins (XIPs). This review provides a concise summary of the fundamental structural and functional characteristics of fungal aquaporins, including their structure, classification, and known physiological roles. While the majority of the current literature has focused on the aquaporin and aquaglyceroporin subfamilies, this review also aims to offer a comprehensive and original overview of the relatively understudied X-intrinsic protein subfamily, highlighting its potential implication in fungal biology.